2005
DOI: 10.4319/lo.2005.50.4.1129
|View full text |Cite
|
Sign up to set email alerts
|

The role of soluble Fe(III) in the cycling of iron and sulfur in coastal marine sediments

Abstract: In marine sediments, Fe(III) is found predominantly as a solid. Recently, however, soluble species of Fe 3ϩ complexed by natural organic ligands have been detected in coastal marine sediments with voltammetric microelectrodes. The role of soluble Fe 3ϩ complexes in diagenesis is unknown. In anoxic conditions, soluble Fe 3ϩ can effectively oxidize FeS 2 and recycle iron and sulfur for use as terminal electron acceptors during natural organic matter (NOM) degradation. Alternatively, soluble Fe 3ϩ complexes can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…FeS and aqueous inorganic S species), and the actual in-situ rates is consistent with several previous studies of pyrite formation in more complex systems. For example, Canfield et al (1998), Carey and Taillefert (2005) and Burton et al (2007) all found that pyrite formation in complex systems (ferrihydrite/bacteria suspensions, estuarine sediments, and Fe(III)-rich soils, respectively) exceeded theoretical rates by several orders of magnitude.…”
Section: Comparison Between the Observed And Theoretical Rates Of Pyrmentioning
confidence: 96%
“…FeS and aqueous inorganic S species), and the actual in-situ rates is consistent with several previous studies of pyrite formation in more complex systems. For example, Canfield et al (1998), Carey and Taillefert (2005) and Burton et al (2007) all found that pyrite formation in complex systems (ferrihydrite/bacteria suspensions, estuarine sediments, and Fe(III)-rich soils, respectively) exceeded theoretical rates by several orders of magnitude.…”
Section: Comparison Between the Observed And Theoretical Rates Of Pyrmentioning
confidence: 96%
“…The voltammetric conditions used in triplicate cathodic square wave voltammetry (CSWV) measurements included preconditioning at Ϫ0.9 V for 10 s and deposition at Ϫ0.1 V for 10 s to concentrate Fe(III) species at the electrode surface. A scan rate of 200 mV s Ϫ1 from Ϫ0.1 to Ϫ1.8 V with a pulse height of 0.05 V was used as previously described (10,59,60,62 ) by CSWV in degassed medium, and the pilot ion method was used to quantify concentrations of Fe(II). Voltammograms were integrated using a semiautomated software program developed for these applications (6).…”
mentioning
confidence: 99%
“…The extensive presence of iron oxides across the Satilla River estuary (not shown) suggests that both processes may have been responsible for the production of these complexes in the sediment. FeS (aq) was detected in the transition zone between iron and sulfate reduction in over 60% of the profiles that contain dissolved sulfides, indicating that iron was chemically precipitated by sulfide in these sediments (Taillefert et al 2002;Carey and Taillefert 2005). Although sediment diagenesis in estuarine sediments typically transitions from manganese and iron reduction (Aller 1980) or even methanogenesis (Martens and Goldhaber 1978) to sulfate reduction along salinity gradients, manganese and iron reduction were significant in most sediments along the Satilla River during the 3 yr of this study.…”
Section: Discussionmentioning
confidence: 96%